Experimental investigation of polyurethane-coated HPFRC panels under direct contact blast - Alžběta Měrková; Přemysl Kheml; Alexandre Perrot; Petr Hála (Acta Polytechnica)
High-performance fibre-reinforced concrete (HPFRC) exhibits exceptional resistance to dynamic loading, making it a promising material for structures exposed to blast or impact events. However, when used to produce thin panels, it can experience scabbing under extreme loads. To address this and enhance the blast resistance, this study explores the application of a polyurethane (PU) coating to the HPFRC panels. Coated and uncoated panels undergo direct contact blast testing and various factors, such as crater area, rear fragment formation, cracking, and residual flexural strength, are analysed. Our study indicates that applying a PU coating to the panels could effectively prevent scabbing and mitigate the risk of complete perforation, while it appears that it results in the panel absorbing more energy during blast, leading to increased damage and a subsequent decrease in residual flexural strength compared to bare panels.